Customization issues in enterprise system implementation project: a case study in banking industry / Azman Hashim - Hashim, Azman (2014)
Enterprise system is widely adopted in most small and large organizations today. In implementing enterprise system in an organization, customization has been considered one of the major factors which have a significant impact on the project. The problem relating to customization can lead to project cost and schedule overrun, and even cause project failure in many cases. The purpose of this research is to explore various issues pertaining to customizations aspect in enterprise system project and derived a framework to present the issues and reasons. The research covers the scope of customization for changes needed to be performed on the standard system.